Act Like a Retailer, Think Like a Brand: An Overview of Retailer Brand Equity and Agenda for Future Research in Indian Context. (March 2016) - Rashmi,; Dangi, Hamendra
There exists a vast body of literature on brand equity (BE). In comparison, research on its application to retailers is scarce and more recent. This review brings together strands from the fragmented literature on BE of retailers. Active research on retailer's equity began only in the recent decade, though earlier scholars have hinted at the existence of the phenomenon previously. Therefore, conceptualisation of retail equity is still in want of consensus. This article synthesises empirical evidence on operationalisation of retailer brand equity (RBE), validation of its frameworks and its antecedent–consequent relationships. We reviewed 160 BE-related papers, a majority of which focused on retail brands. The more relevant of these research articles were published during the years 2003–2014. Results of these researches have been distilled into an integrative model for RBE.